A rede UniCEU e as transformações no território CEU - Di Agustini, Solange de Fátima Andreassa (2019)
This research has as object of study the UniCEU, located in the CEU, offering distance learning higher public education. The distance learning has accumulated a great growth in enrollments since its regulation, mainly in the training of teachers. Faced with this, the cutting of this, is the Pedagogy course, offered at the UniCEU Meninos by Unesp and Univesp. The subjects are: students, coordinator of the center, director and coordinator of UniCEU, community members and CEU staff. The general objective is to understand the reasons that lead to the installation and the provision of higher education courses in peripheral territories of São Paulo city and to understand the importance of access to this stage of education for popular classes. And the specific objectives: characterize the socioeconomic profile of students, identify the motivations to pursue the course, what they think of the distance learning mode, analyze the relevance of "university migrate" from the central territory to the CEUs, identify possible transformations in the territory from the access to higher education, to verify the impact of the course in agents’ life and the technological resources it has for its academic development. Quantitative and qualitative methodologies and data collection instruments were adopted: questionnaire, interview and documentary analysis. The contributions of Bourdieu, Haesbaert, Raffestin and Levy constituted the theoretical reference. It was concluded that: the profile of the students is composed of 20 women and seven men, aged between 24 to 59 years, signaling subjects beyond the expected age for higher education; the reasons for the location of UniCEU and the presence of public university in the peripheral territory is important for access to higher education to popular classes and the analysis of the legislation means that the location of UniCEU was not an isolated initiative but a strategy of cooperation between the entities to achieve PNE targets; the presence of UniCEU in the community provides access to the network territory (Haesbaert, 2004) with the establishment of the center, connecting public universities with the community, enabling cultural and scientific exchange; there is a new territoriality with this inclusive public policy of access to the public university, with benefits to the school community due to the disruptive formation in which universities go to school to train teachers in vulnerable territories. The motivations of the students to pursue higher education in the UniCEU are based on the criteria: location, gratuity, symbolic value of the public university, for being distance learning, professional growth, continuing education and the need of diploma to meet legal requirements